Evaluasi Penerapan Kebijakan Tarif Pajak Progresif Pajak Kendaraan Bermotor Di Kantor SAMSAT Kota Bekasi Tahun 2018-2022 - Prihadini, Diana; Amalia, Annindya Atmi (Jurnal Ilmu Administrasi Publik, 2024)
The role of the vehicle as a means of transportation makes the vehicle a major requirement. With the addition of vehicles each year, it is expected to be able to increase regional income from the taxation sector. One type of local tax revenue is obtained through motor vehicle taxes. Motor vehicle tax is a tax on motor ownership. The phenomenon in this study is that until there is an issue of abolishing vehicle tax fines and the abolition of progressive taxes, this is considered the right way to make people more obedient in paying taxes and to make motorized vehicle data records more valid. The purpose of this study is to evaluate the application of the Progressive Tax rate policy for Motor Vehicle Tax as an effort to increase local revenue at the Bekasi City Samsat Office, as well as the obstacles and efforts faced by the Samsat and Taxpayers in evaluating the implementation of the Progressive Tax rate policy. This research was conducted at the Bekasi City Samsat Office and the informants in this study were Progressive Taxpayers of Motor Vehicle Tax. This study uses a qualitative approach and descriptive research type. Collecting data in this study are observation, documentation, and interviews. The results of this study indicate that the progressive tax on motorized vehicle taxes in Bekasi City has been effective. Based on the theory of Evaluation Criteria according to William N. Dunn (2013, 28-29) which according to him to reassess a policy, criteria are needed, namely Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness, and Accuracy which shows that the overall results have been running according to provisions of the progressive tax rate policy for motor vehicle taxes that apply at the Bekasi City Samsat office. Obstacles experienced by the Bekasi City Samsat Office, such as the lack of counseling on progressive tax collection, which causes a lack of public knowledge regarding the existence of progressive taxes.